The association of serum-free light-chain levels with markers of renal function. (3rd July 2015) - Erdem, Bilge Karatoy; Davran, Fatih; Yilmaz, Vural Taner; Çetinkaya, Ramazan; Akbas, Halide
Abstract: Background : The kidney is often affected in plasma cell dyscrasias, usually due to the effects of nephrotoxic monoclonal-free light chains. Renal failure due to a monoclonal gammopathy may be detected by the highly sensitive serum-free light-chain (sFLC) ratio yet missed by electrophoretic assays. The aim of this study was to assess sFLC levels in relation to markers of renal function. Methods : Five-hundred thirteen patients were included in this study. sFLC levels were measured by Freelite® (The Binding Site Group Ltd, Birmingham, UK) assay using the BNII nephelometer (Siemens Diagnostics, Germany). Kappa/lambda (κ/λ) sFLC ratio was calculated. Serum creatinine levels were analyzed by modified Jaffe method in Cobas 8000 analyser. GFR was estimated by the CKD-EPI (Chronic Kidney Disease Epidemiology Collaboration) equation. Patients were assigned to two groups depending on their eGFR values: ≤60 mL/min/1.73 m 2 (Group 1, n = 103) and >60 mL/min/1.73 m 2 (Group 2, n = 410). Data were expressed as median and min–max. All the statistical analyses were done with SPSS version 20.0 and a significance level of 0.05 was considered. Results : Serum κ-FLC median value was 36.4 (5.62–16, 000) mg/L, serum λ-FLC was 21.7 (4.91–8770) mg/L, κ/λ sFLC ratio was 1.33 (0.01–3258) and serum creatinine was 1.56 (0.63–7.21) mg/dL in Group 1. Both λ sFLC and κ/λ sFLC ratios were correlated with eGFR ( r = −0.318, r = 0.198, p < 0.05, respectively). We did not find any significant correlation between κ/λ sFLC ratio and eGFR in Group 2. Conclusions : We examined the association between sFLC concentrations and renal function. Our preliminary findings suggest that serum λ-FLC might be considered as a useful marker for predicting renal function. Prospective studies are needed to clarify the usefulness of these parameters for identifying renal failure due to a monoclonal gammopathy.